THE ROLE OF WORK LIFE BALANCE, WORKPLACE DISCOMFORT BEHAVIOR, PSYCHOLOGICAL WELL BEING, AND EMPLOYEE ASSISTANCE PROGRAM ON JOB SATISFACTION - Putri Fajar Handayani; J. Joeliaty (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
Psychological pressure is a prevalent issue among employees, which is now openly acknowledged and discussed. The focus on mental health encourages employees to alleviate mental stress, enabling them to have faith in their own capabilities, stay motivated to reach their full potential, and seize opportunities to excel, ultimately leading to job satisfaction. This study aims to investigate the factors influencing job satisfaction. The research methodology employed includes a review of literature and empirical studies found in various books and previous research journals. The findings indicate that Work-life Balance, Workplace Incivility Behavior, Psychological Well-being, and Employee Assistance Program have an impact on Job Satisfaction. Based on the results, it is recommended that organizations prioritize initiatives promoting work-life balance, address workplace incivility behavior through training programs, foster a respectful work environment, and promote psychological well-being through mindfulness practices and stress management programs. Additionally, implementing an effective Employee Assistance Program with counseling services and support can significantly contribute to overall job satisfaction.